2019
DOI: 10.1108/bfj-05-2019-0322
|View full text |Cite
|
Sign up to set email alerts
|

Use of sodium metabisulfite and ascorbic acid as anti-browning agents in processed potatoes

Abstract: Purpose The purpose of this paper is to evaluate the use of sodium metabisulfite (SMB) and ascorbic acid (AA) either alone or in combination as anti-browning agents in industrially processed potatoes. Design/methodology/approach The experiment was carried out in the production line of an agricultural industry located in the state of Paraná, Brazil, testing the following chemical treatments in the immersion process of the potatoes: T1 (control, without additives), T2 (0.5 percent AA), T3 (0.5 percent SMB), T4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
(27 reference statements)
0
9
0
Order By: Relevance
“…Sodium bisulphite addition on garlic powder production tends to decrease ash content. Sodium bisulphite promoted reduction in the pH [10]. In an acidic environment, minerals will bind to organic substances which will loss from material.…”
Section: Proximatementioning
confidence: 99%
See 1 more Smart Citation
“…Sodium bisulphite addition on garlic powder production tends to decrease ash content. Sodium bisulphite promoted reduction in the pH [10]. In an acidic environment, minerals will bind to organic substances which will loss from material.…”
Section: Proximatementioning
confidence: 99%
“…It is most effective than other additives in preventing the green discoloration [6]. Some research result reported that sodium bisulphite can prevent discoloration of pumpkin powder [7] [8], banana [9], apple [9], potatoes [10], green coconut water [11], shallot [12] [13] [14], and garlic [6]. This study aimed to determine the effect of size reduction method and sodium bisulfite concentration on the characteristics of garlic powder from off-grade garlic.…”
Section: Introductionmentioning
confidence: 99%
“…Ready-to-eat processed potatoes goes through the processes of peeling, steaming, sterilization and vacuum packaging (Nascimento and Canteri, 2019), resulting in a product that requires reduced preparation time and characterized by longer shelf-life respect to the fresh vegetable (Capuano and Fogliano, 2011). However, the high sterilization temperature associated with the large amount of reducing sugars and amino acids present in this tuber result in a non-enzymatic browning reaction, called the Maillard reaction, which negatively affects the appearance of processed potatoes (Bethke, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Phenols are oxidized to colorless quinones by PPO, followed by further oxidation of quinones to brown melanin or by polymerization of the quinones, giving rise to pigments of high molecular weight and very dark or black coloring, and losing nutritional value and good appearance (do Nascimento et al, 2019;Illera et al, 2019). How to extend the shelf life of shrimp?…”
Section: Introductionmentioning
confidence: 99%